Media Coverage on Child Sexual Abuse: A Study of Daily Graphic and Ghanaian Times - Kwofie, Daniel (UniMAC-GIJ, 2020)
Child sexual abuse is a global phenomenon with devastating health effects on victims and survivors. It possess health dangers and risks to children worldwide including those in Ghana but the media is known to be an efficient tool to fight it through news coverage. Content analysis was used to gather relevant information from Daily Graphic and Ghanaian Times (2017-2018) which are two most widely read newspapers in Ghana. The study revealed that media coverage on child sexual abuse was inadequate, there were high incidences of intra-familial child sexual abuses and the media also failed to call for policy interventions against child sexual abuse.
MA Journalism